The Covenants of the Prophet and the Subject of Succession - Morrow, John A. (Religions, 2019)
In order to advance their argument that Imām Alī was the divinely and prophetically designated spiritual and political successor of the Prophet Muḥammad, Shīite Muslim scholars have primarily drawn evidence from the Qur'ān and Ḥadīth which was supplemented by reason and rational arguments. Oddly enough, in their quest to legitimize the Caliphate and Imāmate of Ahl al-Bayt, the People of the House of the Prophet, Shīite scholars have generally ignored one of the most important bodies of literature, namely, the letters, treaties and covenants of the Prophet Muḥammad. The following study examines the Messenger of Allāh's Covenants with Christians and Jews in search of previously overlooked material on the subject of succession, shedding light on the state of Islām prior to the definitive rupture of the early Muslim community into Sunnīs and Shīites.